Genome sequences of Pseudomonas spp. isolated from cereal crops - Gardiner, D.; Stiller, J.; Covarelli, Lorenzo; Lindeberg, M.; Shivas, R.; Manners, J. (American Society for Microbiology, 2013)
ï¿½ 2013 Gardiner et al. Compared to those of dicot-infecting bacteria, the available genome sequences of bacteria that infect wheat and barley are limited. Herein, we report the draft genome sequences of four pseudomonads originally isolated from these cereals. These genome sequences provide a useful resource for comparative analyses within the genus and for cross-kingdom analyses of plant pathogenesis.